2023
DOI: 10.1371/journal.pone.0295053
|View full text |Cite
|
Sign up to set email alerts
|

Different PfEMP1-expressing Plasmodium falciparum variants induce divergent endothelial transcriptional responses during co-culture

Basim Othman,
Leo Zeef,
Tadge Szestak
et al.

Abstract: The human malaria parasite Plasmodium falciparum is responsible for the majority of mortality and morbidity caused by malaria infection and differs from other human malaria species in the degree of accumulation of parasite-infected red blood cells in the microvasculature, known as cytoadherence or sequestration. In P. falciparum, cytoadherence is mediated by a protein called PfEMP1 which, due to its exposure to the host immune system, undergoes antigenic variation resulting in the expression of different PfEMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 104 publications
0
12
0
Order By: Relevance
“…Various studies have shown that the cytoadhesion of iRBCs strongly influences the gene expression of the ECs. Among other things, it has been shown that binding to HBEMCs mainly influences the signaling pathways involved in the inflammatory response, apoptosis, cell-cell signaling, signal transduction, and the NF-kB activation cascade (Tripathi et al, 2009; Othman et al, 2023). However, not only does cytoadhesion seem to influence the expression, but it also seems to depend on which Pf EMP1 is presented on the surface of the iRBCs (Othman et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that the cytoadhesion of iRBCs strongly influences the gene expression of the ECs. Among other things, it has been shown that binding to HBEMCs mainly influences the signaling pathways involved in the inflammatory response, apoptosis, cell-cell signaling, signal transduction, and the NF-kB activation cascade (Tripathi et al, 2009; Othman et al, 2023). However, not only does cytoadhesion seem to influence the expression, but it also seems to depend on which Pf EMP1 is presented on the surface of the iRBCs (Othman et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, significant differences were also found between iRBC IT4var14 and iRBC IT4var37 . Among others, atonal bHLH transcription factor 8 ( ATOH8 ), CXCL8 , CXCL10 , VCAM-1 , radical s-adenosyl methionine domain containing 2 ( RSAD2 ), and IL6 were found to be up-regulated in the presence of iRBC IT4var14 after 6 h of co-cultivation, whereas the expression of these genes was down-regulated in iRBC IT4var37 (Othman et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Both PTGIS and PTGS2 are enzymes involved in the biosynthesis of prostacyclin, a bioactive lipid that is produced by vascular endothelial cells and that plays a role in regulation of endothelial inflammation and apoptosis 41 . Furthermore, a study employing a co-culture model of cytoadherence demonstrated differential gene expression of CYP1A1, PTGIS, and PTGS2 between HBMEC incubated with two parasite lines that expressed different PfEMP1s 25 . Prostacyclin (PGI2) is produced through the action of prostacyclin synthase (PTGIS; also known as prostaglandin I2 synthase, PGIS).…”
Section: Expression Of Intermediates Involved In Maintaining Vascular...mentioning
confidence: 99%
“…Although IE derived from malaria patients have exhibited different binding phenotypes, most studies employ well characterized PfEMP1 laboratory strains to investigate cytoadherence and interaction of different PfEMP1 variants to brain endothelial cells 19,[21][22][23][24] . Separate investigations have highlighted the divergent effect of both TNF stimulation and IE cytoadhesion on endothelial transcriptional responses and the pathways they induce 23,25 . IE isolated from peripheral blood of UM and CM patients have been used to study cytoadherence to human brain microvascular endothelial cells (HBMEC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation